The Impact of Brand, Product Quality and Price on Sales Volume of Samana Mart Stores - I Ketut Suardika; Mertyani Sari Dewi (Universitas Pendidikan Ganesha, 2021)
Sales volume is the final result achieved by the company from product sales made by the sales department. Sales volume is calculated based on the assumed target with the realization achieved. Sales volume does not separate in cash or credit, but is calculated as a whole from the total achieved. So if the sales volume increases and distribution costs decrease, the company's profit achievement level increases. On the other hand, if the sales volume decreases, the company's profit will decrease. This study aims to determine the effect of brand, product quality and price on sales volume. This research was conducted at the Samana Mart Store. Data collection techniques using a questionnaire, with a sampling technique to 94 consumers. Data analysis used research instrument test, classical assumption test, multiple linear regression test, determination test and significance test with t test. The results show that the brand has a significant effect on sales volume where the more famous the brand at the Samana Mart Store, the higher the sales volume. The results of the second study, product quality has a significant effect on sales volume, the better the quality of the products owned by the Samana Mart Store, the higher the sales volume. Furthermore, the final result, price has a significant effect on volume, so it can be said that the higher the price, the more competitive the prices offered by Samana Mart Stores, the higher the sales volume.